2014
DOI: 10.3906/sag-1302-122
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of magnetic field exposure on febrile seizure latency, seizure duration, and electroencephalographic recordings in a rat febrile convulsion model

Abstract: This study covers the design, synthesis, characterization, and cytotoxic activity of a series of uracil C-Mannich bases. Among them, one hybrid compound (1), a molecular combination of the potential antimetabolite substituted uracil and nitrogen mustard, having potential alkylating capability, was prepared as a Mannich base. The other compound was synthesized with the replacement of chlorines in the ethyl chains with hydroxyl groups for testing for anticancer activity. Some of Mannich bases having several amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The present study indicated significantly fewer number of events and less sum of scores in the intervention group 2 than other two groups with seizure (both P=0.02), while the difference in the mean threshold in the inter-vention group 2 was statistically similar. Like our findings, other studies found that EMF did not change statistically on the duration of the 1st seizures in mice [27].…”
Section: Discussionsupporting
confidence: 86%
“…The present study indicated significantly fewer number of events and less sum of scores in the intervention group 2 than other two groups with seizure (both P=0.02), while the difference in the mean threshold in the inter-vention group 2 was statistically similar. Like our findings, other studies found that EMF did not change statistically on the duration of the 1st seizures in mice [27].…”
Section: Discussionsupporting
confidence: 86%
“…All these studies clearly show that EMFs applied in the prenatal period have adverse effects on various organs (26,27). However, the effects on the liver of EMF applied in the prenatal period are still unknown, due to the lack of sufficient studies on the subject.…”
Section: Discussionmentioning
confidence: 99%